Safety Assessment of Microbicide 2P23 on the Rectal and Vaginal Microbiota and Its Antiviral Activity on HIV Infection - Gao, Zhengqin; Fu, Rui; Li, Xiaobo; Wang, Ji; He, Yuxian (Frontiers in Immunology, 2021)
Containment of the AIDS pandemic requires reducing HIV transmission. HIV infection is initiated by the fusion of the membrane between the virus and the cell membrane of the host. 2P23 is an effective HIV membrane fusion inhibitor that may be a good entry inhibitor microbicide candidate. This study evaluated the potential of using gel-formulated 2P23 as a topical microbicide to prevent sexual transmission of HIV in the rectum and vagina. Our data revealed that 2P23 formulated in gel is effective against HIV. There was no change in antiviral activity at 25℃ for 4 months or 60℃ for 1 week. In addition, we demonstrated that the 2P23 gel was stable and fully functional at pH 4.0-8.0 and under different concentrations of H2O2. Finally, the 2P23 gel exhibited no cytotoxicity or antimicrobial activity and did not induce inflammatory changes in the rectal or vaginal mucosal epithelium in New Zealand rabbits after 20 mg/day daily rectovaginal application for 14 consecutive days. Despite repeated tissue sampling and 2P23 gel treatment, the inflammatory cytokines and microbiota of the rectum and vagina remained stable. These results add to general knowledge on the in vivo evaluation of anti-HIV microbicide application concerning inflammatory cytokines and microbiota changes in the rectum and vagina. These findings suggest that 2P23 gel is an excellent candidate for further development as a safe and effective pre-exposure prophylactic microbicide for the prevention of HIV transmission.